Obraz świata wartości w dziewiętnastowiecznym czasopiśmiennictwie dla dzieci i młodzieży w ujęciu lingwistycznym - Uździcka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book addresses the issue of the image of the world in nineteenth-century magazines for children and young people, which has not been the subject of systematic research by linguists so far. Methodologically, the monograph falls within the stream of cultural linguistics. Due to the diversity of the excerpted material, the methods applied range from the paradigm of research into the linguistic image of the world to the normative approach to the category of linguistic correctness.
Keywords: prasa dla dzieci i młodzieży; prasa; kategoria pamięci; lingwistyka kulturowa; ojczyzna; 19 w.; homeland; cultural linguistics; memory category; press for children and youth; press